Respuesta :

Answer:

x^4 -3x^3 - 18x^2

Step-by-step explanation:

f(x)= x-6

g(x)=x^2(x+3),

g(x) * f(x) = (x-6) * x^2(x+3)

                = x^2 ( x-6) ( x+3)

FOIL

                = x^2 ( x^2 +3x-6x-18)

 Combine like terms

                = x^2 ( x^2 -3x-18)

   Distribute

               = x^4 -3x^3 - 18x^2

Answer:

x⁴ - 3x³ - 18x²

Step-by-step explanation:

g(x) × f(x)

(x²(x + 3)) × (x - 6)

Expand brackets.

(x³ + 3x²)(x - 6)

x³(x - 6) + 3x²(x - 6)

x⁴ - 6x³ + 3x³ - 18x²

Combine like terms.

x⁴ - 3x³ - 18x²

Otras preguntas